direction - McCormack, Nancy (The dictionary of Canadian law, 2020)
"The fifth edition contains more than 5,450 new and revised entries, including 1,660 new definitions in Aboriginal, environmental, family, insurance, intellectual property, internet/computer, medio-legal, and dozens of other areas of law. The result is this indispensable Canadian legal dictionary that provides judges, lawyers, law students, professors, researchers, and business people with a distinct, one-stop reference to Canadian definitions." –Publisher's description.